A brief overview of the legal system in Turkey - (:unkn) unknown (Springer International Publishing, 2018)
A big part of rights violations arise from the neglect (omission) and/or intentional actions of government officials. Rights violations happen within the chain of command of the hierarchical administrative-political structure. Preparation and active investigation of cases are suspended; the hierarchical superiors protect their juniors with rhetoric and action; legal organs do not make clear decisions, and so on. In terms of the legal process, its glacial pace, the absence of legal enforcement organizations, outside pressure casting shadows of doubt on judicial independence, tendencies and practice that undermine judicial impartiality should be pointed out. Legal practitioners sometimes let nationalistic or moralistic judgments seep into their legal decisions over the central universality of human rights, which make these decisions more political rather than legal or judicial. © Springer International Publishing AG, part of Springer Nature 2019. All rights reserved.
Keywords: Justice; Legal system; Turkey